Efektivitas Komunikasi Perawat terhadap Serah Terima Pasien - Olimpia de Jesus Araujo; Mira Triharini; Ilya Krisnana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the nurse's effective communication effect on patient handover. The method used is a systematic review by tracing articles on ScienceDirect, Ebsco and ProQuest using the terminology